Fighting the Progress of COVID-19 by Enhancing Immunity: A Review of Traditional Sudanese Natural Products Containing Immune-Boosting Elements - O. Abdellatif, Ashraf; A. Eisa Alnoor , Ahlam; M. E. Ali , Eslam; H. A. Alkhalifa , Khalda; M. E. Mohamed, Razan (Journal for Research in Applied Sciences and Biotechnology, 2023)
The World Health Organization has classified the coronavirus disease outbreak as a worldwide pandemic as a result of the COVID-19 expansion. According to medical professionals, individuals with strong immunity often outlive infections more frequently than those with poor immunity. The COVID-19 pandemic has prompted the need for novel approaches to treating the illness and its symptoms. Natural products from plants are increasingly being seen favorably in comparison to synthetic ones in the fight against diseases. As a result, in order to avoid contracting any unanticipated illnesses, individuals must increase their immunity by eating more dietary supplements and by taking drugs that have immune-boosting properties. This review aimed to give a general overview of some traditional Sudanese foods and drinks that are rich in immune-boosting elements, and accordingly, they could be safely recommended as an adjuvant dietary supplement to improve the immune system's ability to fight such infections as COVID-19. Also, this review aims to bring attention to the fact that immune boosters may be found in natural sources, which will help pharmaceutical companies by taking some of the load off of them. Electronic databases, including Google Scholar, Scopus, and the Web of Science, were searched for relevant material. The selected articles underwent independent eligibility and information extraction reviews. The review focused on certain traditional Sudanese herbs and their derivatives that are rich in immune-stimulating vitamins and minerals and therefore could possibly be recommended as immune-boosting dietary supplements to help fight COVID-19. This review highlights the fact that the pharmaceutical sector, especially community and hospital pharmacists, could play a vital role in supporting the healthcare system by encouraging their communities to add plants and their products that are rich in immune-boosting vitamins and minerals to their diet.